Reimaging the role of the information professionals in the Educational process: the case of the Sultanate of Oman - Alkharousi, Rahma Suliman (Advances in Social Sciences Research Journal, 2019)
This research applied a mixed-approach to investigate professionals perceive on their profession and what others expect from them to lead professional organizations setting their core competencies for the future. Furthermore, the research aimed to explore LRCs observes their educational preparation and job practices in building their profession. Besides, it defines the critical restrictions that prohibit them from reimaging their future professional roles within the educational process. Questionnaires are used to explore Omani professionals acquired competencies from learning and work. In addition, the research conducted tow discussion sessions with 10 focus groups to support the quantitative data collected through questionnaires. The quantitative findings indicated that a weak correlation between educational programs and work practices, especially in tasks requiring specialized skills and competencies. The qualitative findings highlighted the Competencies acquired by the information professional from work which are public relations, research skills, and partnership, marketing services skills, dealing with technology, and ways of dealing with the beneficiary. Besides, the findings revealed skills needed by the learning resource specialists as training in updating developments in the field, English language. Negative School staff’s view information profession as multifunction of tasks that are not directly attributed to their occupation as well as far from the LRC regulations. The lack of communication between information professionals and supervisors, the absence of the learning resource specialists at schools in the first cycle of the basic education, the weakness of maintenance of hardware and Internet in schools, incorrect Job Title which is LRC Resource Specialist, are challenges hindered Omani professionals to make improvements in their profession. Accordingly, findings present suggestions to improve the actual status.